Boosting Charge Transport in a 2D/3D Perovskite Heterostructure by Selecting an Ordered 2D Perovskite as the Passivator. Issue 7 (10th January 2023) - Li, Chuanzhao; Zhu, Renlong; Yang, Zhe; Lai, Jing; Tan, Junjun; Luo, Yi; Ye, Shuji
Abstract: We demonstrate that an ordered 2D perovskite can significantly boost the photoelectric performance of 2D/3D perovskite heterostructures. Using selective fluorination of phenyl‐ethyl ammonium (PEA) lead iodide to passivate 3D FA0.8 Cs0.2 PbI3, we find that the 2D/3D perovskite heterostructures passivated by a higher ordered 2D perovskite have lower Urbach energy, yielding a remarkable increase in photoluminescence (PL) intensity, PL lifetime, charge‐carrier mobilities ( ϕμ ), and carrier diffusion length ( L D ) for a certain 2D perovskite content. High performance with an ultralong PL lifetime of ≈1.3 μs, high ϕμ of ≈18.56 cm 2  V −1  s −1, and long L D of ≈7.85 μm is achieved in the 2D/3D films when passivated by 16.67 % para‐fluoro‐PEA2 PbI4 . This carrier diffusion length is comparable to that of some perovskite single crystals (>5 μm). These findings provide key missing information on how the organic cations of 2D perovskites influence the performance of 2D/3D perovskite heterostructures. Abstract : The structural ordering of 2D organic–inorganic hybrid perovskite results in the structural ordering of the 2D/3D perovskite heterostructure and further boosts the excellent optoelectronic properties of the heterostructure films.